The fifteen minute hour : efficient and effective patient-centered consultation skills - Stuart, Marian R.; Lieberman, Joseph A., III (Joseph Aloysius), 1938- (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2019)
The Fifteen Minute Hour is well-established as a classic text, providing invaluable support for primary care practitioners aiming to increase patient satisfaction without adding significantly to the length of a visit. This sixth edition continues to emphasise a patient-centred approach to help practitioners enhance the therapeutic relationship with their patients. With a renewed focus on wellness and health promotion, the book offers simple and effective techniques to solve or prevent psychological and behavioural problems manifested in the consultation. The Fifteen Minute Hour has become essential reading around the world, and this sixth edition is completely updated with brand new case material based on real-world consultations, additional techniques for managing chronic conditions including pain, and new references substantiating the efficacy of the authors' methods.
The BATHE technique : key to making your practice patient-centered -- Broadening the context of the office visit or medical consultation -- Promoting wellness and managin chronic conditions -- Small interventions and why they work -- Therapeutic pearls for brief counseling sessions -- Structuring a fifteen minute counseling session -- Managing difficult patients : their pain and yours -- Accenting the positive : puitting an affirmative spin on the BATHE technique -- Handling special situations, staff, and assurance self-preservation -- Wrapping up : integrating treatments, modifying lifestyles, getting results -- Appendix A: Twelve good questions and three good answers for all seasons -- Appendix B: Recommended books and other resources for patients.
Revised edition of: The fifteen minute hour : therapeutic talk in primary care / Marian R. Stuart [and others]. 5th ed. [2015].
OCLC-licensed vendor bibliographic record.
Keywords: Physician and patient; Sick -- Psychology; Psychotherapy; Primary care (Medicine); HEALTH & FITNESS -- Holism; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL / Family & General Practice